Ultrakratki laserski sunki - Jelerčič, Urška (Obzornik za matematiko in fiziko, 2011)
We discuss ultrafast pulsed laser systems and describe methods of femtosecond and attosecond pulse generation in the case of Ti:sapphire laser. We describe three main techniques, which are used for the formation of pulses: mode-locking of resonator modes, amplification based on frequency modulation, and frequency multiplication. We also present potential improvements expected in the future.
Keywords: fazno vklepanje; frekvenčna modulacija; nelinearna optika; ojačevalno sredstvo; optično ojačevanje; sunkovni laserji